Inversion effects reveal dissociations in facial expression of emotion, gender, and object processing - Pallett, Pamela M.; Meng, Ming (Frontiers in Psychology, 2015)
To distinguish between high-level visual processing mechanisms, the degree to which holistic processing is involved in facial identity, facial expression, and object perception is often examined through measuring inversion effects. However, participants may be biased by different experimental paradigms to use more or less holistic processing. Here we take a novel psychophysical approach to directly compare human face and object processing in the same experiment, with face processing broken into two categories: variant properties and invariant properties as they were tested using facial expressions of emotion and gender, respectively. Specifically, participants completed two different perceptual discrimination tasks. One involved making judgments of stimulus similarity and the other tested the ability to detect differences between stimuli. Each task was completed for both upright and inverted stimuli. Results show significant inversion effects for the detection of differences in facial expressions of emotion and gender, but not for objects. More interestingly, participants exhibited a selective inversion deficit when making similarity judgments between different facial expressions of emotion, but not for gender or objects. These results suggest a 3-way dissociation between facial expression of emotion, gender, and object processing.